1980
DOI: 10.1002/art.1780230502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high and low dose cyclophosphamide therapy in rheumatoid arthritis

Abstract: Eighty-eight patients with active rheumatoid arthritis from 8 Cooperating Clinics were evaluated in a 32-week controlled, double-blind trial comparing 150 mg daily to 75 mg cyclophosphamide daily. Improvement in the arthritis was seen in both groups, and there were no important differences between the two treatment groups in any of the 8 variables used to measure disease activity. Untoward effects were also similar for the two groups. These results differ from preliminary results reported earlier.Cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 15 publications
2
7
1
Order By: Relevance
“…This is in accordance to recent studies that investigate more agressive DMARD regimen (17,24). In another trial with CYC in RA, however, a 30% reduction in tender and swollen joint count and a reduction of morning stiffness for 30 minutes was considered a marked improvement (27). These less stringent criteria might have contributed to the lower rate of withdrawals (less than 10%) after 32 weeks of treatment with 75 mg per day (27), compared to our data.…”
Section: Safety Analysis and Long-term Follow-upsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in accordance to recent studies that investigate more agressive DMARD regimen (17,24). In another trial with CYC in RA, however, a 30% reduction in tender and swollen joint count and a reduction of morning stiffness for 30 minutes was considered a marked improvement (27). These less stringent criteria might have contributed to the lower rate of withdrawals (less than 10%) after 32 weeks of treatment with 75 mg per day (27), compared to our data.…”
Section: Safety Analysis and Long-term Follow-upsupporting
confidence: 92%
“…The results of our analysis are difficult to compare to some other studies, where different sets of outcome parameters were applied. These included morning stiffness, walking time, and grip strength, (14,27) as well as ring size and shoe tying time (14). In our cohort, an improvement of swollen joint count of at least 50% was the precondition to continue the treatment, since only a marked improvement was thought to justify the prolonged exposure to CYC.…”
Section: Safety Analysis and Long-term Follow-upmentioning
confidence: 83%
See 2 more Smart Citations
“…As described in previous studies, no statistically significant relationships were found between adverse effects and the nominal dose or the duration of the therapy [28,29]. Currently, there are some papers which describe a comparable frequency of adverse effects from the use of CP irrespective of the mode of administration [30], but comparing the use of oral or intravenous cyclophosphamide was not a goal of this paper.…”
Section: Discussionmentioning
confidence: 75%